PENGGUNAAN SISTEM BUKU AGENDA ELEKTRONIK DALAM PERSURATAN GUNA MENCAPAI EFISIENSI KERJA KARYAWAN (Studi kasus pada Yayasan Tifa Jakarta) - Slamet Heri Winarno (Universitas Bina Sarana Informatika, 2009)
We know that the use of electronic agenda book as a letter management media contribute in employee efficiency. The work efficiency covered this book are labor efficiency, which requires faster to distribute and search for letters, space efficiency, which letter file cabinet is no longer necessary, cost efficiency which minimize salary, office equipment, , and space rent for document facility.Keywords: Elektronic Agenda BookLetter, Work Efficiency